A DEVELOPMENT NON-INVASIVE HEMOGLOBIN SENSOR BASED ON GIANT MAGNETORESISTANCE WITH INTEGRATED INTERNET DEVICE SYSTEM - Wardoyo, Sony
Hemoglobin plays a crucial role in the human body as an indicator of health conditions. Therefore, detecting hemoglobin levels in the blood is important. The use of invasive diagnostic tools still dominates worldwide, mainly due to their high accuracy in measurements. Invasive hemoglobin diagnostic tools generally have several limitations, including cautious operation (blood sampling from the body) and medical waste generated from disposable materials. On the other hand, many of these tools have not yet been integrated with internet-based devices, which have become the forefront standard in measurement flexibility. This dissertation research aims to address the aforementioned issues by developing a non-invasive hemoglobin sensor integrated with an internet-based device system. The method employed to develop the non-invasive approach involves magnetization and detection on blood vessels beneath the skin surface, specifically on the finger. This method operates based on the magnetization of Fe ions in hemoglobin, which is then detected using a magnetic sensor, scientifically referred to as magnetic plethysmography (MPG). The equipment used to magnetize Fe atoms in hemoglobin consists of neodymium magnets with a magnetic field strength of B > 1 T, while detection is performed using giant magnetoresistance (GMR)-based magnetic field sensors. The steps undertaken in the research are as follows: 1) development of GMR sensors for hemoglobin detection, 2) design and construction of a blood magnetizer, 3) instrumentation sensor circuitry, 4) integration of internet device system with the sensor, 5) simulation of blood vessel flow detection, and 6) direct testing of the hemoglobin sensor on the finger surface. The research results revealed that the blood magnetizer design was produced using neodymium cylinder-type magnets, generating a magnetic field of B = 1.05 T, and two combinations of block-shaped permanent magnets resulted in a magnetic field of B = 1.3 T. The sensor system based on giant magnetoresistance utilized components from the NVE series AA002-02, with instrumentation amplification provided by the INA118P, enhancing the sensor detection output. Upon application in the simulation of blood vessel flow using a microfluidic device with FeCl3 solution, both the magnetizer and sensor functioned effectively, yielding good measurement accuracy. In non-invasive hemoglobin measurements, the sensor performed well in detecting deoxyHb compared to oxyHb. Based on the correlation values between invasive and non-invasive methods, it was found that using the 1.05 T magnetizer, the positive correlation was deoxyHb > oxyHb, while with the 1.3 T magnetizer, the positive correlation remained consistent with deoxyHb > oxyHb. This implies that using a magnetic field > 1 T induces magnetization effects on Fe ions in hemoglobin, particularly in venous blood vessels compared to arteries. Measurement and IoT monitoring of non-invasive GMR hemoglobin sensors worked well on the surface veins of the finger. The IoT hemoglobin monitoring results showed that the correlation value of deoxyHb > oxyHb was 0.8920 compared to 0.6746. Furthermore, the accuracy of measurement conversion results ranged around 1 g/dL for each increase in invasive measurement. The GMR sensor has the advantage of not generating medical waste, making it potentially environmentally friendly for future development as a diagnostic tool. The results of this research can provide new insights into non-invasive hemoglobin level measurements based on the magnetic properties of blood, offering potential as an alternative to reduce the impact of medical waste in the future.